Managing mental health difficulties in higher education: the lived experience - East, Carole Ann Margaret (2013)
1.6 million young people are currently in higher education (HEFCE, 2010). Even though participation ‘stands at 57% for the 20% most advantaged...compared to 19% for the most disadvantaged 20 %’( Inside Government, 2011), this is an increasingly diverse population. Among the attendant pressures for both students and staff, mental health concerns predominate: since the Royal College of Psychiatrists published their first report into the mental health of students, (RCP, 2003), the issues ‘highlighted have shown no signs of abating and in many respects have become more pressing’ (RCP. 2011:17).